2018
DOI: 10.1038/s41598-018-25698-w
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell imaging of nuclear–chromosomal dynamics in bovine in vitro fertilised embryos

Abstract: Nuclear/chromosomal integrity is an important prerequisite for the assessment of embryo quality in artificial reproductive technology. However, lipid-rich dark cytoplasm in bovine embryos prevents its observation by visible light microscopy. We performed live-cell imaging using confocal laser microscopy that allowed long-term imaging of nuclear/chromosomal dynamics in bovine in vitro fertilised (IVF) embryos. We analysed the relationship between nuclear/chromosomal aberrations and in vitro embryonic developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…5b). Our results and the success of pregnancy after time-lapse imaging in the mouse/bovine embryo 12,25 suggest that karyotyping without biopsy can be applied to livestock embryos. In contrast, our technology involves injecting mRNA encoding fluorescent protein and laser irradiation for excitation, making it difficult to directly apply to human embryos.…”
Section: Relationship Between Micronuclei Formation and Blastocyst/armentioning
confidence: 67%
“…5b). Our results and the success of pregnancy after time-lapse imaging in the mouse/bovine embryo 12,25 suggest that karyotyping without biopsy can be applied to livestock embryos. In contrast, our technology involves injecting mRNA encoding fluorescent protein and laser irradiation for excitation, making it difficult to directly apply to human embryos.…”
Section: Relationship Between Micronuclei Formation and Blastocyst/armentioning
confidence: 67%
“…Although micronuclei-like structures have been detected in bovine embryos previously (Yao et al, 2018), their prevalence or whether they were associated with a particular stage of preimplantation development was not determined. To address this, we generated a large number (N=53) of bovine embryos by in vitro fertilization (IVF) and fixed them at the zygote to blastocyst stage to evaluate DNA integrity with DAPI and nuclear structure by immunostaining for the nuclear envelope marker, LAMIN-B1 (LMNB1; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While micronuclei-like structures have been previously detected in bovine embryos (Yao et al, 2018), we were able to assess their prevalence throughout preimplantation development and follow their fate in subsequent mitotic divisions. Of the cleavage-stage bovine embryos examined by immunostaining or live-cell imaging, over ~30% contained micro- or multi-nuclei and anaphase lagging of chromosomes was detected in certain embryos prior to micronuclei formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine embryos for ET are usually evaluated by the IETS codes [6,7] whose accuracy relies on the proficiency of the operators. Sugimura et al [4,11] showed that high-quality bovine embryos could be selected using morphokinetic indicators such as timing, number of blastomeres at first cleavage, and number of blastomeres at the onset of the lag phase as well as by observing nuclear/chromosomal abnormalities of bovine embryos using live-cell imaging technology [19].…”
Section: Textmentioning
confidence: 99%